Two Cases of Composite Pheochromocytoma-Ganglioneuromas With Plasma Metanephrine Levels in the Subclinical Range Pheochromocytoma-Ganglioneuroma - Mayssam El Najjar, MD; Elie Naous, MD; Caroline Blake; Aysegul Bulut, MD; Alexander Perepletchikov, MD; Ann T. Sweeney, MD (AACE Clinical Case Reports)
Background/Objective: In <10% of cases, pheochromocytomas coexist with other tumors, most commonly ganglioneuromas, and are termed composite pheochromocytoma-ganglioneuromas. We present 2 cases of composite pheochromocytoma-ganglioneuromas and review the diagnosis and management of these rare tumors. Case Report: Patient 1 and patient 2 were 35-year-old and 45-year-old woman, respectively. Patient 1 presented with a history of controlled hypertension and symptoms of anxiety along with palpitations, diaphoresis, and flushing. Patient 2 complained of abdominal pain and underwent abdominal computed tomography (CT) imaging. Patient 1 and patient 2 had metanephrine levels of 76 pg/mL and 61 pg/mL (normal <57 pg/mL), respectively, and normetanephrine levels of 161 pg/mL and 116 pg/mL (normal < 148 pg/mL), respectively. CT scans depicted right adrenal masses in both cases: patient 1 had a 2.3 × 2.6 cm mass measuring 36 Hounsfield units on noncontrast CT imaging and patient 2 had a 4.5 × 3.5 cm right adrenal mass measuring 73 Hounsfield units on contrast CT imaging. Both patients underwent laparoscopic robotic adrenalectomies without complications. The pathologic analyses of both cases revealed composite pheochromocytoma-ganglioneuroma tumors. Surveillance at 1 year in both patients demonstrated no evidence of recurrence. Discussion: The clinical and radiological presentation of composite pheochromocytoma-ganglioneuromas mirrors pheochromocytomas. The diagnosis relies on histopathological analysis. Treatment of pheochromocytoma-ganglioneuromas is complete surgical excision in a high-volume center with adrenal expertise and is associated with an overall excellent prognosis. The probability of recurrence is low, and distant metastases have rarely been reported. Conclusion: Pheochromocytoma-ganglioneuromas may present with plasma metanephrine levels in the subclinical range. As with isolated pheochromocytomas, lifetime surveillance is critical for composite pheochromocytoma-ganglioneuromas.